Students' Views On Digital Technologies In Learning English For Specific Purposes (ESP) In University - Yelliza, Yelliza (Fakultas Sastra Universitas Ekasakti, 2025)
This study explores university students’ perspectives on the use of digital technologies (DT) in learning English for Specific Purposes (ESP). While the integration of DT has been widely promoted, student perceptions remain underexplored, particularly in vocational higher education. The aim of this research is to examine students’ opinions on the role of DT in enhancing ESP learning and to identify the tools they frequently employ. A mixed methods design was applied with twelve participants from different study programs. Quantitative data were obtained through a Likert-scale survey on perceptions and digital tool usage, complemented by brief interviews for qualitative insights. Results indicate strong support for DT integration: 91.7% of students agreed or strongly agreed that DT enhances ESP learning, with no negative responses recorded. WhatsApp and YouTube were universally used (100%), followed by Zoom (91.7%), Google Classroom (66.7%), and Moodle (50%). Use of ESP-specific simulators was less common (33.3%). Students highlighted ease of access, interaction, and flexibility as key benefits, while limited exposure to specialized ESP tools was noted as a challenge. The study concludes that students hold positive views of DT in ESP, yet further investment in domain-specific applications is required to optimize learning outcomes.